The effect of COVID-19 on autonomic nervous system function in American football athletes - Rifat, S.; Miller, B.; Chung, E.; Johnson, P.; Sarna, K. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: SARS CoV-2, the respiratory virus causing COVID-19, is known to affect many organs and systems. Although most healthy, immune competent athletes fully recover, some continue to experience long term symptoms. Little is known about the causative mechanism of this phenomenon, however emerging evidence suggests that cardiovascular autonomic dysfunction may play a role. Autonomic dysfunction can manifest in many ways including disturbances in blood pressure, resting heart rate (RHR) and Heart Rate Variability (HRV). These parameters can be easily measured with popular wearable devices. To our knowledge this is the first study to prospectively investigate the effect of COVID-19 on cardiac autonomic function in American football players by using a commercially available wearable device. METHODS: Forty American football players from the same team were enrolled in this prospective matched cohort study. Twenty who recovered from COVID-19 who were cleared to play after normal physical examination and normal cardiac testing (hs-troponin, echocardiography and cardiac MRI), and a matched cohort of 20 who were antigen negative at baseline and never tested positive for COVID-19 throughout the study period. All participants underwent 6-times per week COVID-19 testing throughout the study period. The control group was matched based on position including the following three groups; Linemen (L), Large Skill (LS) and Small Skill (SS). All participants wore a multi-sensor wrist device (WHOOP Inc., Boston, MA) that measured RHR, HRV, respiratory rate (RR) and hours sleep (HS) per night throughout a 6-week period during their competitive season. Statistical analyses were performed to evaluate the association between each individual categorical characteristic variable and COVID-19 history. Difference scores from last and baseline values for the entire study duration were calculated. General linear model analysis was done considering COVID-19 infection status and player position. RESULTS: Twenty-nine players completed the study. Eleven were removed, 8 from the COVID-19 cohort and 3 controls because they did not wear the wrist band long enough to acquire a baseline. There was no statistically significant difference between the groups apart from the LS subgroup with a higher body mass index for the COVID-19 group (p=0.0460). Throughout the study period there was a statistically significant difference (p=0.0434) between RHR mean for the SS group with a higher mean of the mean in the COVID-19 cohort compared to the control group. There was no statistically significant difference between player position groups for any other variables. CONCLUSION: COVID-19 does not appear to have significant long-term effects on HRV, RR and HS in American football players who fully recovered from COVID-19. Although the study group size was small, elevated RHR in the Small Skill group may indicate prolonged autonomic dysfunction after COVID-19 in these lean, highly conditioned athletes.